Structure driven compound optimization in targeted protein degradation. (December 2020) - Leissing, Thomas M.; Luh, Laura M.; Cromm, Philipp M.
Graphical abstract: Abstract : Small molecule induced protein degradation has created tremendous excitement in drug discovery within recent years. Not being confined to target inhibition and being able to remove disease-causing protein targets via engagement and subsequent ubiquitination has provided scientists with a powerful tool to expand the druggable space. At the center of this approach sits the ternary complex formed between an E3 ubiquitin ligase, the small molecule degrader, and the target protein. A productive ternary complex is pivotal for a ubiquitin to be transferred to a surface lysine of the target protein resulting in poly-ubiquitination which enables recognition and finally degradation by the proteasome. As understanding the ternary complex means understanding the degradation process, many efforts are put into obtaining structural information of the ternary complex and getting a snapshot of the underlying conformations and molecular contacts. Locking this transient trimeric intermediate in a crystalline state has proven to be very demanding but the obtained results have tremendously improved our understanding of small molecule degraders. This review discusses target protein degradation from a structural perspective and highlights the evolution of certain degraders based on the obtained structural insights.